Developing L2 interactional competence: increasing participation through self-selection in post-expansion sequences. Issue 3 (2nd September 2017) - Watanabe, Aya
Abstract: Using longitudinal conversation analysis as a methodological framework, this study documents the development of second language (L2) interactional competence by focusing on a recurrent interactional practice observed in an English as a foreign language (EFL) classroom. Through observing a novice L2 learner's developing methods of participation in recurrent post-expansion sequences, the study aims to reveal the trajectory of how his interactional practices and use of interactional resources change over time. The data comes from four episodes of his second and third year of learning English. The analysis shows that the learner increases his interactional competence in terms of turn-taking strategies, use of linguistic and non-linguistic resources, and display of relevancy and appropriateness when taking self-selected turns. The development of L2 interactional competence is displayed through the learner's increased ability to monitor the details of the ongoing talk and his appropriate use of interactional resources. The findings contribute to recent CA investigations into the developmental process of L2 interactional competence through detailed longitudinal analysis.